Objective measurements of skin surface roughness after microdermabrasion treatment - Zapletalova, A; Pata, V; Janis, R; Kejlova, K; Stoklasek, P (Skin research and technology, 2017)
BACKGROUND: The aim of this article is to present a new methodology for assessment of skin topology using a three-dimensional image (3D). METHODS: The measurement of the skin surface roughness is based on 3D scanning of silicone replicas by chromatic aberration length technique in a contactless manner, i.e. by a polychromatic light beam. Analysis of the skin surface reprints was performed using Talymap, Gold version. Results were analysed by fractal geometry, which allows to evaluate changes of the skin surface before and after application of cosmetics and instrumental cosmetological techniques. The methodology was applied for objective assessment of the effects of diamond microdermabrasion on the skin surface roughness. Measurements were performed on 23 volunteers in the age group of 31-67 years. RESULTS: Based on the results of skin surface scanning after the treatment with diamond microdermabrasion it may be concluded that inequalities of the skin surface are reduced immediately after exfoliation. However, this effect mostly diminishes within 14 days after treatment. The entire study ultimately suggests that the instrumental method used only leads to improvement of the skin surface immediately after its application. Thermo vision images of the skin surface temperature were obtained during the application of the abrasive method. The experimental results showed that the skin is rather cooled than heated by the treatment. CONCLUSION: This study is focused on the development of a methodology for objective measurement of changes in treated skin relief using 3D scanning. The results are evaluated using fractal dimension. The output may also include also an enlarged model of the skin surface made by 3D printer, which can serve for illustrative communication with the client.
Keywords: dospělí; Humans; kůže; lidé středního věku; kosmetické přípravky; Middle Aged; zobrazování trojrozměrné; Dermatologic Surgical Procedures; Cosmetics; Skin Aging; stárnutí kůže; Skin; Surface Properties; Adult; výsledek terapie; dermatochirurgické výkony; Treatment Outcome; ženské pohlaví; dermabraze; Imaging, Three-Dimensional; lidé; Dermabrasion; povrchové vlastnosti; Aged; senioři; Female